ANALISA POLA TRANSAKSI PENJUALAN IKAN DI TPI BRONDONG LAMONGAN - Nur Nafi’iyah; Retno Wardhani (STMIK YADIKA BANGIL, 2017)
Abstract: How is the relationship between fish data one with other fish in sales at TPI Brondong Lamongan. An analysis of the linkage of fish sales to one another using Apriori. And to see the linkage and sales pattern using confidence value 40% and support value 50%. The total data analyzed were 140 records of transactions, and the analyzed fish, they were: Tongkol, Togek, Kuniran, Teri, Kakap Merah. From the result of this research produce pattern, that is if buying of Cowkol then definitely buy Togek, and if buy Togek then buy Teri. The confidence value is rounded to 1 digit behind the comma. Keywords: Pattern, Apriori, Fish.